Peran Satuan Lalu Lintas Kota Tanjung Balai dalam Upaya Penanggulangan Pelanggaran Lalu Lintas oleh Anak - Suriani, Suriani; Silaban, Herman (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to determine the role of the Tanjung Balai City Police Traffic Unit (Satlantas) in dealing with traffic violations involving children in the jurisdiction of Tanjung Balai City. This research uses empirical legal research methods. This study identifies the strategies and actions implemented by Traffic Police to prevent and take action against violations committed by children. Data shows that the number of traffic violations by children will fluctuate between 2021 and 2023, in 2021 there will be 34 children, in 2022 there will be 5 children and in 2023 there will be 40 children, of which the most serious violations involve traffic accidents that harm other people. by causing death and with the most common violations being the absence of a driving license (SIM) and the use of standard restraints. The Tanjung Balai City Traffic Police carried out various law enforcement efforts, including humane warnings and education about the importance of obeying traffic regulations. Enforcement procedures vary based on the type of violation, with a restorative justice approach also being considered in cases that harm other parties.